Lucien, Torquemada et les « merveilles » des mondes cervantins - Nicolas Correard (Atalaya)
To what extent can we consider Cervantes as a Lucianic writer, who took the Menippean satirist as a model? The question remains open, in spite of the numerous studies that have already been dedicated to the subject. We shall propose here a reassessment of a precise point, i.e. the representation of marvellous phenomena in the Colloquy of the Dogs, the Second part of Don Quijote and the Persiles. Adding to the already identified sources, we shall underline the inspiration that Cervantes may have drawn not only from the True Stories, but also from the Philopseudes (The Lover of Lies), which could locate his work in the line of Humanistic satire of superstitious credulity, notwithstanding some transfers. We shall then consider an alternative source from which Cervantes drew abundant mirabilia, the Jardín de flores curiosas by Antonio de Torquemada, not as a contradictory, but as a complementary hypothesis: as the polygrapher held these prodigies for semi-fictions, the novelist could transplant them into ironic, Lucian-like narratives, in order to show that wonders were the product of the fascinated imagination of his characters.